(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cyanide a name given the most deadly and sinister chemical poison known to man. It can be in gas form or solid or even liquid. Human kind has been taking cyanide in small doses in a natural way. It is found in the chemical composition of human body even in vegetables or certain gases as well. This poison is extremely deadly in a twisted sense as it cannot be detected easily due to its odorless nature. It leaves few to no traces of its presence, that is why cyanide has become a efficient tool for suicides and murders and various other crimes. The concern of this paper is to focus on the essential fundaments of cyanide, what it is, what is its composition and the medico legal aspect of such poisoning. The following paper will deal with the certain aspects of cyanide poisoning.